Antimicrobial drug utilization pattern in a tertiary level intensive care unit in Northern India: Antimicrobial Stewardship Programme need of the hour - Banday, Muddasir; Manzoor , Muntaha; Mohammad Akbar Shah; Zulfiqar Ali; Ahmad, Nazir; Zulfkar Qadri (Asian Journal of Medical Sciences, 2023)
Background: Antimicrobial drugs are the most frequently prescribed drugs in hospital settings with intensive care unit (ICU) patients showing the highest consumption of these drugs. Antimicrobial overuse and misuse is attributed to antimicrobial resistance (AMR). AMR in coming years will emerge as a global pandemic, maiming the modern health-care system. High consumption of antimicrobial drugs is one of leading factors contributing to AMR. Aims and Objectives: This study aimed at evaluating the prescription pattern of antimicrobial drugs in ICU and estimates the burden of inappropriate antimicrobial drug utilization in ICU settings of a tertiary level teaching hospital. Materials and Methods: The current study was conducted on 100 patients over a period of 6 months, admitted in surgical ICU (SICU), and neuro SICU (NICU) of a tertiary level hospital in Jammu and Kashmir, India. Study patients were identified through daily review of pharmacy records and antimicrobial drugs prescribed for the initial 5 days of ICU admission were documented in a well-designed questionnaire consisting all the necessary information regarding antibiotic therapy. Results: Out of the 100 enrolled study subjects, 98% received an empiric therapy. Majority of the patients were given a combination antimicrobial therapy during the initial 5 days of ICU admission. The most common antibiotic prescribed as monotherapy was ceftriaxone during the initial 2 days of ICU stay followed by piperacillin-tazobactam and meropenem in the next 3 days. Amikacin was the most frequently prescribed antibiotic in combination therapy during first 2 days followed by vancomycin in the consecutive days. A total of 27 antimicrobial drugs belonging to 15 classes were prescribed to the study participants during the initial 5 days of ICU admission. Conclusion: The study reports a very high consumption of antimicrobial drugs in ICUs with maximum of antimicrobial therapies prescribed empirically. A robust action plan, consisting of proper protocol for prescribing empiric antimicrobials, regular monitoring of antibiotic consumption in ICUs with a system of prospective audit, and feedback and timely interventions are a keystone of good antibiotic stewardship and should be the focus in ICU and NICU.